2016
DOI: 10.17644/sbd.237580
|View full text |Cite
|
Sign up to set email alerts
|

Beden Eğitimi Öğretmen Adaylarının Bilişötesi Öğrenme Stratejileri, Akademik Öz-Yeterlikleri ve Öğretmenlik Mesleğine Yönelik Tutumları

Abstract: the female pre-service PE teachers were higher than male participants, and the scores of the participants from the MLSS, the ASES and the TPAS did not differ significantly regarding their grade levels. Additionally, significant positive correlations were observed between the scores of the MLSS, the ASES and the TPAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Öztas (2018) found that the participants' "psychological" and "relaxation" subdimension scores of leisure satisfaction were statistically significantly higher in favor of female participants. Küçük et al (2016), on the other hand, it was concluded that the scores of female participants were significantly higher in the "relaxation" sub-dimension of leisure satisfaction.…”
Section: Yöntemmentioning
confidence: 93%
“…Öztas (2018) found that the participants' "psychological" and "relaxation" subdimension scores of leisure satisfaction were statistically significantly higher in favor of female participants. Küçük et al (2016), on the other hand, it was concluded that the scores of female participants were significantly higher in the "relaxation" sub-dimension of leisure satisfaction.…”
Section: Yöntemmentioning
confidence: 93%
“…After the diagnosis of the covid-19 cases in Turkey, education in all universities was suspended for a short period of time, and then it was decided by the Higher Education Institution of Turkey that distant education would continue via digital means in universities as of March 23, 2020 [21]. Studies on the self-sufficiency of the students of the faculty of sports sciences are present in the literature [22][23][24][25][26][27]. When the literature related to general belief of self-sufficiency and burnout variables was examined, a negatively significant correlation between burnout and self-sufficiency beliefs was revealed [28][29][30].…”
Section: Introductionmentioning
confidence: 99%